Bronchodilatory effect of Myxopyrum serratulum in animal model (Bangladesh Journal of Pharmacology, 2017)
The plant Myxopyrum serratulum is traditionally claimed to relieve asthma and cough. The present study was undertaken to evaluate the bronchodilatory effect of the methanolic extract of M. serratulum on histamine-induced bronchospasm by in vivo and the inhibitory effect of the extract on histamine-contracted tracheal chain and ileum by in vitro guinea pig model. Additionally, the relaxant effect of four cumulative concentrations of the extract (0.25, 0.5, 0.7 and 1.0 g%) was assessed using precontracted tracheal chain under different conditions. The extract (400 mg/kg) prolonged the preconvulsive time to 102.3 ± 3.8 sec when compared to saline and standard chlorpheniramine maleate as 121.3 ± 4.5 sec (p